Waste management in Mongolian hospitals - Popp, Walter; Jigjidsuren, Altantuya; Badarch, Ulambayar; Uyanga, Tsogtbaatar; Ross, Birgit; Zorigt, Khand; Spors, Jörg; Bodart, Claude (International Journal of Infection Control, 2014)
An overview is given about waste handling in hospitals in Mongolia. Basically, handling of waste is regulated according to international standards. But in reality there are several problems, specially outside of the capital Ulaanbaatar. The situation is described, examples of problems are given and also some proposals are made how to improve the situation.